Irregular shape anchor in cohesionless soils - Niroumand, Hamed (Butterworth-Heinemann, 2017)
Irregular Shape Anchors in Cohesionless Soils presents a new type of soil anchor that can significantly lower cost and preparation time for application in low cohesion soils. The experimental data provided helps readers design and implement the new devices for their projects. The author introduces the specific problem of soil anchors in low cohesion soils in chapter one. In chapter two, a literature review is presented comparing findings of previous researchers and positioning irregular shape anchors (ISA) within the most traditional types of soil anchors. In chapter three, the methods used for testing ISA are presented together with the specific properties of sands, anchor materials, and the model of the fracture mechanism. The experimental results are covered in chapter four, including comparisons in embedment ration and sand density. The failure mechanism is discussed both for loose and dense sands. In chapter five, the author compares the experimental data with the theoretical and computational results. In chapter six, the author presents his conclusions and recommendations on the usage of ISA to projects. Researchers in geotechnical engineering can use the methods and models presented in the book for their own projects. Practicing engineers will benefit from the compiled experimental data and comparisons with most traditional types of soil anchors. Introduces a new type of soil anchorOffers a thorough literature review on soil anchor typesPresents design specifications and practical data that can be used in new projectsProvides engineers with a way to save implementation time and costs in geotechnical projects.